Characterization of the complete mitochondrial genome of Agapornis personatus and its phylogenetic analysis. Issue 2 (3rd July 2019) - Chen, Yun-Xia; Hou, Sen-Lin; Zhou, Yong-Wu; Huang, Ya-Lin
Abstract: In this study, we characterized the complete mitochondrial genome of Agapornis personatus . Its mitochondrial genome is a circular molecule of 16, 722 bp, with all genes exhibiting typical mitochondrial gene arrangement and transcribing directions. The overall base composition is 21.49% T, 34.6% C, 29.66% A, and 14.25% G. Phylogenetic analysis of the complete mitogenome was conducted using the neighbour-joining method based on 16 parrot species. Phylogenetic tree suggested that A. personatus was closest to the same genus specie Agapornis roseicollis . The results would be useful for further studies on molecular evolution and breeding works of A. personatus .